Expression and translocation of glucose isomerase as a fusion protein in E. coli - SARIYAR AKBULUT, BERNA (My University, 2004)
Glucose isomerase of Thermus thermophilus was fused to maltose binding protein to use its signal sequence and slow folding characteristic for transport to the periplasm in Escherichia coli. The product was mostly retained in the cytoplasm and 1.6% of the total glucose isomerase activity was detected in the periplasm as a fusion protein. The effect of inducer concentration on translocation was insignificant, however induction at 23°C increased periplasmic glucose isomerase fusion by 50%. Growth medium was supplemented with amino acids to investigate their effect on translocation. Addition of 0.5% (w/v) alanine, the most abundant amino acid in the glucose isomerase sequence, increased expression by 24%, and induced extracellular secretion of the fusion protein by 18%. On the other hand, glycine retarded growth and caused lysis. The elevated pH of cultures with alanine indicated its possible effect of on translocation, but no significant change was observed by externally imposed pH variations. These results indicate that the secretion efficiency of a fusion protein depends on the characteristics of the system used. © 2004 Elsevier Inc. All rights reserved.
Keywords: Fusion protein; Glucose isomerase; Maltose binding protein; Translocation